2014
DOI: 10.1080/03057240.2014.943166
|View full text |Cite
|
Sign up to set email alerts
|

ACED IT: A tool for improved ethical and moral decision-making

Abstract: Numerous examples of unethical organizational decision-making highlighted in the media have led many to question the general moral perception and ethical judgments of individuals. The present study examined two forms of a straightforward ethical decision-making (EDM) tool (ACED IT cognitive map) that could be a relatively simple instrument for organizations to improve the moral and EDM of its members. Results revealed that participants utilizing either form of ACED IT were more likely to identify a moral dilem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The ACED-IT is a structured cognitive tool (Kreitler et al, 2009;Kreitler et al, 2014) which requires participants to fill in the blanks requesting specific information related to the problem situation (see Figure 1). ACED-IT stands for Assess, Create, Evaluate, Decide, Implement, and Test.…”
Section: Aced-itmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACED-IT is a structured cognitive tool (Kreitler et al, 2009;Kreitler et al, 2014) which requires participants to fill in the blanks requesting specific information related to the problem situation (see Figure 1). ACED-IT stands for Assess, Create, Evaluate, Decide, Implement, and Test.…”
Section: Aced-itmentioning
confidence: 99%
“…Indeed, research has demonstrated that identifying causes and forecasting potential consequences are vital activities involved in making an ethical decision (e.g., Stenmark et al, , 2010. Research comparing the ACED-IT form and expressive writing has shown that while engaging in expressive writing does results in improved indices of ethical decision-making, the ACED-IT form often results in the best cognitive processing regarding the ethical problem (Kreitler et al, 2014;Stenmark & Kreitler, 2017. Thus, while there is evidence that expressive writing as a technique can influence the way people think about and approach an ethical problem, most evidence suggests that the ACED-IT form is superior to expressive writing with regard to the cognitive aspects of ethical decision-making.…”
Section: Expressive Writingmentioning
confidence: 99%
“…ACED-IT. The cognitive processes involved in thinking through an ethical dilemma were measured using the cognitive tool ACED-IT (Kreitler et al, 2009(Kreitler et al, , 2012a(Kreitler et al, , 2012b(Kreitler et al, , 2014. The ACED-IT is a structured tool that requires participants to fill in the blanks answering specific questions about the problem at hand.…”
Section: Measurementmentioning
confidence: 99%
“…The ACED IT is a structured map (Kreitler et al, 2009(Kreitler et al, , 2012a(Kreitler et al, , 2012b(Kreitler et al, , 2014 that uses a 'fill-in-the-space' method to organise written information (see Figure 1). On the front of the map, participants describe the ethical dilemma, note practical issues, identify individuals affected by the dilemma, and organise a decision team.…”
Section: Aced-itmentioning
confidence: 99%
“…Finally, the present study examined participants' perception of the ethical situation, to determine if those perceptions might be impacted by pressure. This tool is a structured map (Kreitler et al, 2009(Kreitler et al, , 2012a(Kreitler et al, , 2012b(Kreitler et al, , 2014 in which participants fill in the blanks eliciting specific types of information relevant to the problem at hand (see Figure 1). ACED IT stands for Assess, Create, Evaluate, Decide, Implement, and Test.…”
Section: Introductionmentioning
confidence: 99%